PERAN TURKIYE SEBAGAI MEDIATOR TERHADAP KONFLIK RUSIA-UKRAINA TAHUN 2022 - Raihan, M. Fadli Ar; Retnaningsih, Umi Oktyari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
The escalating conflict between Russia and Ukraine in 2022 has drawn global attention. Turkey, as a country with geographical proximity and diplomatic relations with both parties, has taken on a significant role as a mediator in efforts to resolve this conflict. This research aims to analyze Turkey's role as a mediator, its effectiveness, and the national interests underlying its involvement. Using qualitative methods and a descriptive-analytical approach, data was collected through a literature study from various secondary sources. The research findings indicate that Turkey has been actively mediating through the organization of diplomatic meetings, facilitation of peace negotiations in Istanbul, and involvement in the Black Sea Grain Export Initiative alongside the UN. Although these efforts have not yet succeeded in halting the conflict entirely, Turkey has managed to open communication channels between the involved parties. In addition to humanitarian factors, Turkey's involvement is also driven by economic interests, domestic political considerations, and geopolitical ambitions as a regional power. This mediation role not only strengthens Turkey's international image but also highlights the importance of diplomacy by neutral states in armed interstate conflicts. Keywords: Turkey, Mediation, Russia-Ukraine Conflict, National Interests.